The Role of Metacognition and Motivation in Developing the Writing Skill: the Case of Second Year Students of English at University “des Frères Mentouri” Constantine 1 - Sahli, Fatiha (Journal of Human Sciences, 2017)
Writing has an effective role in learning any language. It is a basic skill that endorses language acquisition, fosters critical thinking and permits students to communicate. Moreover, it becomes an essential competence for the learner to communicate in the globalized world and to achieve academicsuccess. This study is a fulfillment of the urgent need to make students aware of some metacognitive strategies that facilitate the writing task. It seeks to explore the efficiency of implementing metacognitive strategies via the use of the Process Approach in English Foreign Language writing classes to develop the students’ written production. Two main tools are used which are the teachers and the students questionnaires, and a quasi- experimental research (pre test and post test). During the experimental study, the researcher used metacognitive strategies and taught the participants in the experimental group how to use them in their writing skill. Through this study, the researcher has attempted to create a motivating environment and aid the learners to write essays following the different recursive stages of the Process Approach as a metacognitive strategy. However, the participants in the control group did not receive any treatment during their writing practice. The results show that the written compositions of the experimental group are highly improved compared to the control group.